Pelatihan Khutbah Jumat Pada Santri Pondok Pesantren Modern Fatimah Azzikra Paluh Nipah Pematang Cengal Tanjung Pura - Muhammad Ilham; Al Qadri, Muamar (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
The Friday Sermon is a sermon held before the Friday prayer. Fatimah Azzikra Islamic Boarding School is one of the Islamic boarding schools located in II Paluh Nipah hamlet, Pematang Cengal village, Tanjung Pura subdistrict, Langkat district. At this Islamic boarding school, the students have never had any training to learn Friday sermons. In this cottage there is a subject called "muhadoroh". This subject is one of the boarding school subjects which discusses how children are trained to be proficient in giving speeches, lectures and sermons. But the material to train students to deliver Friday sermons has not yet arrived. Because the researchers want to hold Friday sermon training at this Islamic boarding school. The method used in Community Service (PkM) is qualitative using a descriptive approach. The results of community service are: the steps in presenting the material, namely, first the presenter opens with an expression of gratitude to Allah and blessings on the Prophet Muhammad SAW, then explains the material about the Friday sermon through infocus (power point), in addition to explaining There was also a question and answer session between the presenter and the training participants. After the material was presented, the presenter asked one of the participants to practice the Friday sermon and after that the presenter corrected any discrepancies in the implementation of the Friday sermon such as voice, expression, etc.